2009
DOI: 10.1097/bot.0b013e31819b35db
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Platelet-Rich Concentrate With Bone Graft Materials: An In Vitro Study

Abstract: The data obtained from these in vitro investigations demonstrate that the cellular responses induced by PRC and bone graft materials in hBMSC can be significantly (positively or negatively) modified by adding the agents in combination. These in vitro data highlight the need to consider the potential interaction between biologic agents when added in combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Butcher et al found a signifi cant increase in DNA content and mineralization level by adding PRP to DBM in vitro. 67 Likewise, a viable osteochondral construct has been created with DBM and PRP ex vivo. 249 In contrast, Ranly et al found a neutral or even inhibitory eff ect of PRP to the ectopic formation of bone induced by DBM in a nude mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Butcher et al found a signifi cant increase in DNA content and mineralization level by adding PRP to DBM in vitro. 67 Likewise, a viable osteochondral construct has been created with DBM and PRP ex vivo. 249 In contrast, Ranly et al found a neutral or even inhibitory eff ect of PRP to the ectopic formation of bone induced by DBM in a nude mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The basis for the thyroid surgery was founded by Theodor Billroth and Theodor Kocher, between 1873 and 1893, that standardized and precise anatomical dissection with preliminary ligation of the two principal arteries of the gland on each side, followed by excision of the gland[1]. …”
Section: Introductionmentioning
confidence: 99%
“…Pieske et al demonstrated in their clinical study, using autologous bone graft versus DBM in the internal fixation of ununited long bones that the application of DBM compared to iliac crest autologous bone grafting led to a better outcome and simultaneously to a decreased quantity of adverse effects [116]. The combination of DBM and PRP increases the proliferation of human bone marrow stromal cells (hBMSC), as well as the osteoblastic differentiation and bone formation compared with PRP alone [117] or DBM alone [118]. …”
Section: Methodsmentioning
confidence: 99%